PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI FABEL BERBANTUAN KINEMASTER ERHADAP KETERAMPILAN MENYIMAK BAHASA INDONESIA PADA KELAS IV SEKOLAH DASAR - Rahmadani, Dzikra; Muhammadi; Adrias; Muhammad Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Listening skills are a crucial aspect of language proficiency to be cultivated in elementary school students. However, observations in several elementary schools indicate that Indonesian language instruction remains dominated by lecture methods and textbook usage, preventing students' listening skills from developing optimally. This study aimed to develop valid, practical, and effective animated fable video learning media using the KineMaster application to enhance the listening skills of fourth-grade elementary school students. The study employed the Research and Development (R&D) method using the ADDIE development model, comprising the analysis, design, development, implementation, and evaluation stages. The research subjects included expert validators, teachers, and fourth-grade elementary school students. Data were collected through observations, interviews, questionnaires, and tests, and subsequently analyzed using descriptive quantitative methods. The results demonstrated that the developed media achieved an average validity score of 94.5% (categorized as